2015
DOI: 10.1111/anu.12356
|View full text |Cite
|
Sign up to set email alerts
|

Feed processing affected the digestibility of carbohydrate sources for douradoSalminus brasiliensis

Abstract: Carbohydrate utilization by fish varies with feeding habits and feed processing. Extruded aquafeeds have increased digestibility of carbohydrate sources resulting from the cooking and gelatinization of this nutrient, making it readily available for all aquatic species. This study aimed at determining the effects of extrusion cooking of feeds in the digestibility of different dietary carbohydrate sources for dourado. Isonitrogenous and isoenergetic diets (530 g kg−1 crude protein and 20.80 MJ kg−1 gross energy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
7
0
3
Order By: Relevance
“…The relatively low levels of optimal dietary carbohydrate recorded in the present experiment might be attributed to the raw corn starch used in the formulated diets. It has been demonstrated that the appropriately cooked or gelatinized starch can be effectively utilized by aquatic species as an energy source (Kumar et al., ; Moro, Silva, & Cyrino, ; Stone, Allan, & Anderson, ). The gelatinized corn starch might provide a more digestible feed source for A. japonicus (Xia, Gao et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low levels of optimal dietary carbohydrate recorded in the present experiment might be attributed to the raw corn starch used in the formulated diets. It has been demonstrated that the appropriately cooked or gelatinized starch can be effectively utilized by aquatic species as an energy source (Kumar et al., ; Moro, Silva, & Cyrino, ; Stone, Allan, & Anderson, ). The gelatinized corn starch might provide a more digestible feed source for A. japonicus (Xia, Gao et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal level of 10% lipid in diet was adequate for growth of hybrid tilapia reared in fresh water according to previous studies (El-Sayed and Garling, 1998;Chou and Shiau, 1996). Although lipids and carbohydrates are available for fish, lipid metabolism is reported to be highly modulated by dietary carbohydrates (He et al, 2015;Moro et al, 2015;Zhou et al, 2015;Tran-Duy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…O trânsito gastrointestinal da digesta foi avaliado no ano de 2007 quando Braga e colaboradores verificaram que a partir da segunda hora depois da alimentação ocorre redução gradativa do conteúdo estomacal e após 18 horas todo o trato gastrointestinal se exauri completamente (Braga et al, 2007). A partir do ano de 2008 os trabalhos realizados com o dourado foram mais direcionados para ensaio de digestibilidade de ingredientes e níveis de substituição de farinha de peixe na dieta (Braga et al, 2008;Corrêa, 2016;Moro et al, 2015) (…”
Section: Douradounclassified